An electron spin resonance and photoluminescence investigation of the effect of annealing temperature on Gd-doped La2Zr2O7 nano-ceramics. Issue 7 (August 2015) - Mohapatra, M.; Rajeswari, B.; Hon, N.S.; Kadam, R.M.; Keskar, M.S.; Natarajan, V.
Abstract: Lanthanum zirconate pyrochlore (La2 Zr2 O7 =LZO) is considered as a potential ceramic host matrix for nuclear waste immobilization. In this context, incorporation of Gd ions, a surrogate for trivalent minor actinides, in the LZO host was investigated. Undoped and Gd doped LZO samples were synthesized using a low temperature gel-combustion route and characterized using X-ray diffraction (XRD), scanning electron microscope (SEM), dynamic light scattering (DLS), electron spin resonance (ESR) and photoluminescence (PL) spectroscopic techniques. It was observed that even at 500 °C, a single phase pyrochlore could be stabilized without any impurity phase. The average particle size of the synthesized product was estimated to be 85–90 nm. At lower temperatures, it was observed that, the Gd ions were present mostly on the surface of the LZO host which diffused into the lattice and replaced the La 3+ ions after annealing at 700 °C for 5 h. Due to difference in the ionic radii, the environment around the Gd ion was highly asymmetric. This was further confirmed by PL investigations wherein upon excitation with UV radiation, the nano ceramics exhibited strong and sharp transition at 310 nm suggesting the existence of Gd 3+ ions in a D 2d geometry. Upon annealing, agglomeration of the particles was taking place reducing the surface defects and increasing the PL intensity as well as life time values.